2017
DOI: 10.1017/s1041610216001769
|View full text |Cite
|
Sign up to set email alerts
|

Leisure activities, education, and cognitive impairment in Chinese older adults: a population-based longitudinal study

Abstract: Late-life leisure activities protect against cognitive impairment among elderly Chinese people, and the protective effects are more profound for educated elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
105
5
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(125 citation statements)
references
References 67 publications
6
105
5
9
Order By: Relevance
“…In addition to education and social network, the present study showed that engaging in leisure activities was another environmental factor that protected against the risk of cognitive impairment among men. This result was supported by earlier studies, including studies from China, showing positive effects of involvement in cognitively challenging leisure activities . Functional disabilities had a very small impact on gender differences.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition to education and social network, the present study showed that engaging in leisure activities was another environmental factor that protected against the risk of cognitive impairment among men. This result was supported by earlier studies, including studies from China, showing positive effects of involvement in cognitively challenging leisure activities . Functional disabilities had a very small impact on gender differences.…”
Section: Discussionsupporting
confidence: 82%
“…This result was supported by earlier studies, including studies from China, showing positive effects of involvement in cognitively challenging leisure activities. 12,24 Functional disabilities had a very small impact on gender differences. This is easily understandable, as disabilities naturally increase as people age, regardless of gender.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive function was only assessed with a Chinese version of the MMSE, but not a comprehensive clinical diagnosis. The MMSE is a brief measure of global cognitive function, which may not be sensitive enough to detect early stage of cognitive impairment . However, testing other cutoff points 25 and 27 for mild impairment in the current study did not result in meaningful change of all findings (results not shown).…”
Section: Discussioncontrasting
confidence: 58%
“…The MMSE is a brief measure of global cognitive function, which may not be sensitive enough to detect early stage of cognitive impairment. 36 However, testing other cutoff points 25 and 27 for mild impairment in the current study did not result in meaningful change of all findings (results not shown). Moreover, as with any longitudinal study, attrition owing to the loss to follow-up tends to be a problem in this study.…”
Section: Sensitive Analysescontrasting
confidence: 53%
“…Many studies have shown that older adults who rarely participated in mental or social activities had a higher risk of cognitive decline . A high level of social interactions is beneficial for maintaining cognitive function, and participating in a diversity of activities can reduce the mortality of dementia .…”
Section: Discussionmentioning
confidence: 99%